2020
DOI: 10.3390/w12082136
|View full text |Cite
|
Sign up to set email alerts
|

Are Water User Associations Prepared for a Second-Generation Modernization? The Case of the Valencian Community (Spain)

Abstract: This work focuses on the situation of the technological transition to new technologies in drip irrigation in the Valencian Community (Spain). The study covers the last decade with data from interviews to managers of Irrigation Communities in 2010 and 2018. We analyze the main technological problems in seven topics: (i) Catchment & Pumping; (ii) Storage & Regulation; (iii) Treatment & Filtering; (iv) Transport & Distribution; (v) Maneuver, Regulation & Protection; (vi) Automation; (vii) Thef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…In addition to the notable increase in energy consumption, the massive adoption of drip irrigation sponsored by the public sector has generated other problems in the region. One of those most frequently identified, as other authors have already highlighted [48,61], is the theft of metallic materials from new infrastructures (rated as the third problem in predominantly drip areas), which adds unforeseen costs to the O&M tasks. However, aside from the infrastructure, during the workshops, farmers' representatives criticized the infrastructural bias of the modernization mission.…”
Section: Beyond the Infrastructurementioning
confidence: 99%
“…In addition to the notable increase in energy consumption, the massive adoption of drip irrigation sponsored by the public sector has generated other problems in the region. One of those most frequently identified, as other authors have already highlighted [48,61], is the theft of metallic materials from new infrastructures (rated as the third problem in predominantly drip areas), which adds unforeseen costs to the O&M tasks. However, aside from the infrastructure, during the workshops, farmers' representatives criticized the infrastructural bias of the modernization mission.…”
Section: Beyond the Infrastructurementioning
confidence: 99%
“…The authors of [21] showed that, in the irrigated district of Baixo Acaraú in Brazil, the implemented IAS improved water irrigation management in most areas when farmers followed the advised crop irrigation requirements. The authors of [22] observed an increase in the use of ICT for irrigation management at the WUA level in the Valencian community of Spain, particularly in large, irrigated districts mainly driven by the scarcity of the water resources. Regarding the use of ICT in Tunisia, the agricultural sector presents the biggest potential in terms of development and could largely benefit from its usage [23].…”
Section: Introductionmentioning
confidence: 99%